EPS7-like Enterobacteria phage Isolated from Indonesia - Akhirta Atikana; Katsutoshi Fujita; Alex Prima; Yopi; Hiroko Kawasaki; Ken-Ichiro Suzuki; Puspita Lisdiyanti (Microbiology Indonesia, 2021)
Bacteriophages are the most abundant entities in earth. The order Caudovirales is the largest and most widespread group among bacterial viruses. The purpose of this study is to characterize bacteriophages from Indonesian environment. During this experiment, we collected sample from Kuningan (West Java) and Buleleng (Bali), Indonesia. We used an overlay agar method with three strains of E. coli as a host (NBRC 13965, NBRC 12713 and NBRC 13168) combined with digestion profiling using three restriction enzymes (PvuII, EcoRV and HincII) and transmission electron microscope (TEM) to characterize the morphology of the phage from Indonesia. Our results showed that phage LIPI13-Bp006 is in a group of Caudovirales and highly similar to Enterobacteria phage EPS7.